Molecular Biology: genes to proteins - Trop Burton E (New Delhi Jones and Bartlett, 2012)
Molecular Biology: Genes to Proteins, Fourth Edition provides readers with a comprehensive guide through the basic molecular processes and genetic phenomena in both prokaryotic and eurkaryotic cells. Written for the undergraduate and first-year graduate students of molecular biology, molecular genetics, or biochemistry, the text has been updated with the latest data from this ever-changing field. Whenever possible the author uses a discovery approach, urging students to explore the historical and experimental evidence relevant to the important concepts discussed and to examine clues and develop hypotheses that ultimately lead to advances in molecular biology. Divided in to six Sections, topics are strategically arranged to cover basic information that is necessary to understand more advanced topics covered in later Sections.
Includes index
Keywords: Molecular Biology; Biochemistry